Pemikiran Sukarno di sebalik konfrontasi Indonesia 1959-1965: Suatu tinjauan psikologi politik - Purnama, Chandra (2015)
Confrontation was one of the major policies employed by the Indonesian government under the direct command of President Sukarno against Malaysia from 1959 to 1965 which affected Indonesia domestically and internationally. Indonesian’s Confrontation policy was synonym with Sukarno because he was in fact the main actor that triggered the policy. Therefore, explanation to the Confrontation should not ignore the role of Sukarno’s thought. This case was parallel to the perspective of political psychology which assumed that human behavior related to what human contemplated. There was no study, however, to understand the Confrontation by Sukarno from the psychological aspects of thinking. Thus the research objectives are to analyze the various aspects of Sukarno’s thought behind the Confrontation that encompass beliefs, perceptions, emotions, and tendencies. Various aspects of Sukarno’s thought was referred to the political psychology perspective on the role of beliefs and perceptions in foreign policy decision-making and the principles of trilogy of minds: cognition, affection and conation. This research utilize qualitative method based on the content analysis of Sukarno’s speeches. Analysis carried out deductively to get themes for categories and inductively to get more themes for the new category. The study finds that in Sukarno’s beliefs, the source of conflicts come from the practices of colonialism, imperialism and neocolonialism by the Netherlands, United States and its allies and the local parties that supported liberalism. Their actions were seen as threats to the independence of Indonesia and evoke Sukarno’s dislike emotion. Sukarno had always urged Indonesia to fight against neocolonialism and imperialism and he didi not hesitate to use military forces if possible. More over, it turns out that Sukarno re-evaluated his own policy in which he admitted to the failure of Confrontation policy. However, he also managed to strengthen Indonesian nation-state and pursued consistently the policy to oppose imperialism and neocolonialism. Thus, Indonesia under Sukarno's confrontation policy can be understood through the psychological aspects of his thinking. The consistency of relationships exists among Sukarno’s psychological aspects and also between his thoughts and his actions